Worker Surveillance Capital, Labour Share and Productivity - Philippe Askenazy (Institute of Labor Economics (IZA), 2020)
This paper proposes a basic model with two types of capital: productive capital directly involved in the production process and capital devoted to monitoring workers. Surveillance capital intensifies workers' job strain, while wage recognition encourages their engagement. Firms face a double trade-off between the two types of capital and between incentives and labour costs. Under simple assumptions, up to a certain threshold, technological innovation improves productivity, wages and profits at the same pace, leading to a at labour share in income. Then, once the threshold is breached, profit-maximization initiates a transfer from productive capital to monitoring tools. This progressive shift generates a decline in the labour share and a productivity slowdown, despite greater job strain. The model suggests the possibility of a third phase in which productivity and wages recover.
Keywords: O33; O40; J20; J30; 330; declining labour share; productivity slowdown; effort-reward imbalances; surveillance